Accuracy-velocity relationship and physical characteristics in cricket ball throwing - Hussain, I.; Bari, M. A.; Khan, A.; Mohammad, A.; Ahmad, A. (International Journal of Sports Science and Engineering, 2011)
It is widely accepted and has been documented that velocity has influence on throwing accuracy negatively or positively. However, no published researches have been documented, identifying the velocity and accuracy throwing skill in cricket. Thus, the study was designed to assess the relationship between segmental lengths, accuracy, and velocity of cricket ball throwing ability of cricket players. The ex-post-facto design was used to form the samples as, 10 junior and10 senior cricket players. The age of the junior players were between 14- 18 years, while that of the senior players were above 18 years of age. The physical characteristics of height (Mean: 169.4-172.4cm)), weight (57.8-61.3), segmental length (25.54-38.48). Ten attempt for each throwing techniques (under-arm; side-arm and over-head throws) were recorded using Sony DV cameras in a field setting with (1/2000 shutter speed and at 30-60fps). The cameras were set-up on a rigid tripod and secured to the floor in the location. First camera was located to obtain maximum accuracy and second camera located to view the throwing performances, at given specified distance in the reconstruction of the two dimensional co-ordinate. The location of camera were chosen so that the optical axes of camera intersected perpendicularly to the designated plane. The accuracy of throwing performances were considered in identify the footage for addition and were subjected to analysis. Only one successful and one unsuccessful performance were considered from ten attempts. The statistical analysis revealed no insignificant differences in the throwing accuracy and velocity of the ball and no significant relationship between the upper and lower body segments of the junior and senior cricket players. These indicate that there is no particular body segment that contributes to throwing ability independently. Therefore there is a need for the cricket players to improve on their throwing skills through specialized practice for different throws, through a well harnessed daily programme. Also, coaches need to study each players throwing mechanics in order to correct, where necessary, for better throwing performances.